Non-operative versus operative treatment of suprasyndesmotic ankle fractures: protocol for a prospective, multicentre, randomised controlled trial - Wender Figved; Frede Frihagen; Jan Erik Madsen; Ola Saatvedt; Martin Riiser; Marius Molund; Håvard Furunes (BMJ Open)
Introduction Surgery is widely recognised as the treatment of choice for suprasyndesmotic ankle fractures, because of the assumption that these injuries yield instability of the ankle joint. Stability assessment of ankle fractures using weightbearing radiographs is now used regularly to guide the treatment of transsyndesmotic and infrasyndesmotic ankle fractures. Patients with a congruent ankle joint on weightbearing radiographs can be treated non-operatively with excellent results. Weightbearing radiographs are, however, rarely performed on suprasyndesmotic fractures due to the assumed unstable nature of these fractures. If weightbearing radiographs can be used to identify suprasyndesmotic fractures suitable for non-operative treatment, we may save patients from the potential burdens of surgery.Our aim is to compare the efficacy of operative and non-operative treatment of patients with suprasyndesmotic ankle fractures that reduce on weightbearing radiographs.Methods and analysis A non-inferiority randomised controlled trial involving 120 patients will be conducted. A total of 120 patients with suprasyndesmotic ankle fractures with an initial radiographic medial clear space of <7 mm will be subjected to weightbearing radiographs. If the tibio-talar joint is completely reduced, we will randomise in a 1:1 ratio to either operative treatment including reduction and fixation of the syndesmosis or non-operative treatment with an orthosis. The primary study outcome is patient-reported ankle function and symptoms as measured by the Olerud-Molander Ankle Score at 2-year follow-up. Secondary outcomes include the Manchester-Oxford Foot Questionnaire, range of motion, radiographic results and rates of adverse events.Ethics and dissemination The Regional Committee for Medical and Health Research South East, group A (permission number: 169307), has granted ethics approval. The results of this study will provide valuable insights for developing future diagnostic and treatment strategies for a common fracture type. The findings will be shared through publication in peer-reviewed journals and presentations at conferences.Trial registration number NCT04615650.